Water conservation plans for a hard laterite terrain - a case study - NIMITHA B; Sreekanth J; Vini Babu; Er. Renukakumari J (Guide) (Tavanur 2006 Kelappaji College of Agricultural Engineering and Technology)
Water conservation plans for a hard laterite terrain - a case study
Water conservation plans for a hard laterite terrain - a case study